ISSUES OF DRINKING WATER SUPPLY FOR THE POPULATION DURING MARTIAL LAW (USING THE EXAMPLE OF UKRAINIAN CITIES WITH A POPULATION OF OVER 100,000 PEOPLE LOCATED WITHIN PRYCHORNOMORSKYI ARTESIAN BASIN) - Руденко, Ю.Ф.; Юркова, Н.А.; Гураль, О.В.; Саприкін, В.Ю. (Institute of Geological Sciences, NAS of Ukraine, 2025)
After the start of military operations in Ukraine, the issue of providing the population with drinkingwater became particularly acute due to the lack of stable functioning of a modern centralizedwater supply system in emergency situations. Given the high potential risks of massive armeddamage to urban agglomerations with high population density and infrastructure facilities withinresidential areas, reliable provision of the social structure with drinking water is one of the mostimportant factors in ensuring the life of the population.The article considers scientific, methodological and practical aspects of organizing local (wellroom) water supply for the population during natural and man-made emergency situations, aswell as military operations. Using the example of cities with a population of over 100,000 inhabitants,located within the Black Sea artesian basin, it was analyzed the basic principles of usinggroundwater for the purpose of organizing local water supply for the population.The purpose of the research is development of recommendations aimed at increasing thereliability of water supply to the population based on the creation of local systems of protectedwell room water supply with groundwater or surface water of drinking quality during emergenciesor martial law.The results of the analysis and generalization of geological, hydrogeological and hydrochemicaldata for cities of Ukraine, which are located within the Prychornomorskyi artesian basin, with apopulation from 284 thousand people (Kherson) to 1016 thousand people (Odesa) are presented.Their provision with approved operational reserves or predicted resources of groundwater is determined.For local water supply of these cities during military operations or emergency naturalor man-made situations, it is necessary to attract from 2.0 to 7.0 thousand m3/day of groundwateror surface water. Recommendations are provided for the creation of an extensive networkof local (well room) water supply. Proposals have been developed for the cities of Kherson andMykolaiv that can be implemented by attracting groundwater, and for the city of Odesa – surfaceand groundwater. The research is funded by the National Academy of Sciences of Ukraine. Theirimplementation is planned for 2023–2025.